(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The study aimed to assess the establishment of Faidherbiaalbida transplants under the effect of irrigation intervals and plantingspacing in the field conditions. It consisted of three irrigation intervals of5, 10 and 15 days and three planting spacings of 1x1 m, 1x2 m, and 2x3m; and it was conducted in the premises of the Forest Research Center,Khartoum, during May 2008 to June 2009. The results showed that thetemporal growth rate of F. albida shoot heights was greater in winter(November-February), but it was seriously slowed during the summerperiod (March-June). The shoot height, diameter and biomass growth ofF. albida increased with decreasing irrigation intervals; the growth ofthese parameters was highest in 5 days interval and lowest in 15 daysinterval. Planting spacings had no direct definite effect on F. albidaseedlings’ growth parameters. Even though, in the longer irrigationintervals, transplants’ growth tented to be greater in the wider spacing.Root biomass development seemed to be higher in the longer irrigationinterval regimes. There were no significant differences in the foliarnutrient content of the transplants between the different irrigationintervals. The values of mineral elements measured in this study areindicative of moderate nutrient supply for the F. albida transplants